2017
DOI: 10.1136/sextrans-2017-053153
|View full text |Cite
|
Sign up to set email alerts
|

Perceived intentional transmission of HIV infection, sustained viral suppression and psychosocial outcomes among men who have sex with men living with HIV: a cross-sectional assessment

Abstract: Intervention programmes for MSM living with HIV who thought they were infected intentionally are warranted and should aim to attenuate depressive symptoms and sexual compulsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the present meta-analysis, the first study to report the prevalence of depression in MSM was the article of Mills et al [ 55 ], and the most recent study which measured the prevalence of depression in MSM was the article of Clark et al [ 32 ]. The highest number of studies was related to 2018 with 14 articles [ 26 , 31 , 34 , 46 , 47 , 50 , 58 , 60 , 62 , 69 , 71 , 77 , 84 , 89 ] and 2017 with 11 articles [ 28 , 30 , 38 , 40 , 41 , 43 , 54 , 56 , 67 , 70 , 73 ]. The smallest sample size was related to the study of Armstrong et al [ 25 ] with 56 people, and the highest was related to the study of Tomori et al [ 71 ] with 11,771 people.…”
Section: Resultsmentioning
confidence: 99%
“…In the present meta-analysis, the first study to report the prevalence of depression in MSM was the article of Mills et al [ 55 ], and the most recent study which measured the prevalence of depression in MSM was the article of Clark et al [ 32 ]. The highest number of studies was related to 2018 with 14 articles [ 26 , 31 , 34 , 46 , 47 , 50 , 58 , 60 , 62 , 69 , 71 , 77 , 84 , 89 ] and 2017 with 11 articles [ 28 , 30 , 38 , 40 , 41 , 43 , 54 , 56 , 67 , 70 , 73 ]. The smallest sample size was related to the study of Armstrong et al [ 25 ] with 56 people, and the highest was related to the study of Tomori et al [ 71 ] with 11,771 people.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, participants in a study conducted in Botswana did not perceive high HIV severity because respondents believed people on ARVs do not necessarily increase risky sexual behaviors [ 48 ]. A study of HIV-positive MSM in the Southeastern and Midwestern US indicated that depressive symptoms and compulsive sexual behaviour were more highly associated with beliefs in intentional transmission of HIV [ 49 ]. Suggestively, sexual compulsivity was also expressed by multiple participants in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Different attitudes towards the diagnosis of HIV/AIDS by the PLHIV were identified, based on reports from health professionals. It is noted that feelings of revolt may be present, reflecting the desire to intentionally transmit the virus to others, 13 with unprotected sexual activities or the abuse of substances such as alcohol and drugs. 14 It is noted that other PLHIV, in turn, develop a posture of imprisonment because, due to the stigma and prejudice rooted in HIV/AIDS and so present to this day, they may lose the will to live or to fight for their life and treatment, which can have negative social consequences.…”
Section: It Has Become a Chronic Disease Like Any Other Such As Hypementioning
confidence: 99%